Priceless, ground-based data for solar flare observers. (Research'eu results magazine)
We know that the chromosphere is where most solar flare radiations originate from, but gaps do remain in our understanding of their relevant physics. A consortium led by the University of Glasgow recently made an important contribution in this regard : using both space-based and ground-based data, it defines where future efforts should be targeted, and identifies where long-standing ideas about how energy travels through the solar atmosphere in a flare are in agreement-or disagreement-with observations.